The Effectiveness of Webtoon in Enhancing Past Verbs for Junior High School Students - Friska Amelia; Yohanes Gatot Sutapa Yuliana; Rahmani, Eka Fajar (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study investigated the effectiveness of using Webtoon to enhance English vocabulary mastery among eighth-grade students at SMPN 1 Siantan. A one-group pretest-posttest design of pre-experimental was employed, with 33 students selected through cluster random sampling. Data were collected using pre-tests and post-tests in the form of multiple-choice test. The analysis of the t-test results indicated a significant improvement in students' mastery of past verbs after the use of Webtoon in instruction. The calculated t-test value was 22.595, which substantially exceeded the critical t-table value of 1.694. This statistical outcome led to the rejection of the null hypothesis and the acceptance of the alternative hypothesis, confirming that Webtoon had a positive impact on students' understanding of past verbs. Additionally, the effect size was determined to be 3.91, signifying a substantial effect. These results underscore the effectiveness of incorporating Webtoons into the teaching strategy for enhancing students' English vocabulary, particularly in mastering past verbs.